2021
DOI: 10.1155/2021/8199095
|View full text |Cite
|
Sign up to set email alerts
|

Injection Rate-Dependent Deflecting Propagation Rule of Hydraulic Fracture: Insights from the Rate-Dependent Fracture Process Zone of Mixed-Mode (I-II) Fracturing

Abstract: Mixed-mode (I-II) fracturing is a prominent mechanical characteristic of hydraulic fracture (HF) deflecting propagation. At present, understanding the effect of injection rates on HF deflecting propagation remains challenging and restricts the control of HF deflecting propagation bearing tensile and shear stresses with fluid injection rates. Our recently published experimental results show that the fracture process zone (FPZ) length of mixed-mode (I-II) fractures in rock-like materials increases with the risin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…When the hydraulic fracture extends along the approximate horizontal principal stress direction, the influ-ence of the maximum horizontal principal stress on the hydraulic fracture trajectory increases gradually. Xing et al [20] proposed the influence of injection rate on fracture deflection; the increase in injection rate is similar to the increase in injection pressure in cases 3-5. But their research did not involve the effect of stress difference, perforation angle, fracturing fluid viscosity, etc.…”
Section: The Deflection Of Hydraulicmentioning
confidence: 94%
See 1 more Smart Citation
“…When the hydraulic fracture extends along the approximate horizontal principal stress direction, the influ-ence of the maximum horizontal principal stress on the hydraulic fracture trajectory increases gradually. Xing et al [20] proposed the influence of injection rate on fracture deflection; the increase in injection rate is similar to the increase in injection pressure in cases 3-5. But their research did not involve the effect of stress difference, perforation angle, fracturing fluid viscosity, etc.…”
Section: The Deflection Of Hydraulicmentioning
confidence: 94%
“…Experiment results have shown that with the loading rate increasing, the length of fracture process zone increased from about 5 mm to 17 mm. Fast fluid injection inhibits the deflecting of NF (natural fracture), allowing HF to propagate along the initially designed direction [20]. Yang et al used dynamic caustics in conjunction with high-speed photography to investigate the interaction of running fractures by obliquely incident blast stress waves, which revealed that the moving fracture intended to deflect away from the blast wave source when the fracture and stress wave have the same direction; however, it will propagate toward the blast wave source when they have opposite direction [21].…”
Section: Introductionmentioning
confidence: 99%
“…Rocks. The fracture process zone is a nonlinear development zone in front of the macrofracture, which could be regarded as a plastic zone roughly [42][43][44][45]. In the hydraulic fracturing of reservoirs, the fracture process zone will be generated ahead of the hydraulic fracture, as shown in Figure 10.…”
Section: The Length Of Fracture Process Zone In Different Brittlementioning
confidence: 99%